Enhancing quality attributes of fiber-enriched strawberry juice by application of vanillin or geraniol. (October 2016) - Cassani, L.; Tomadoni, B.; Viacava, G.; Ponce, A.; Moreira, M.R.
Abstract: In this work, the impact of adding prebiotic fibers (inulin, oligofructose and apple fiber) to strawberry juices on quality properties was investigated. Additionally, the beneficial effects of natural preservatives (vanillin and geraniol) on quality parameters of fiber-enriched juices were studied. Microbiological, physicochemical and sensorial properties were evaluated throughout two weeks of storage at 5 °C. Results showed that the addition of prebiotic fibers significantly increased antioxidant capacity and successfully maintained sensory quality of strawberry juice when compared to fresh control. Vanillin and geraniol treatments had a marked effect in reducing native microflora counts (4–6 log cycles reductions) in comparison to untreated samples. Natural preservatives imparted strong flavor in fiber-enriched strawberry juices, however, it was pleasant for those samples treated with vanillin. Besides, overall visual quality scores in treated samples were maintained in the acceptability level throughout storage. Juices with vanillin showed the highest total phenolic content, indicating high nutritional value of the product. Nevertheless, both preservatives agents exhibited lower antioxidant activity than controls. Thus, prebiotic fibers could enhance nutritional and sensory quality of strawberry juice. Also, geraniol and vanillin could be feasible alternatives to improve microbiological quality with low impact on the organoleptic properties of fiber-enriched strawberry juice. Highlights: Prebiotic fibers were added to strawberry juices to improve nutritional properties. Impact of vanillin and geraniol on quality parameters of enriched juice was studied. Added fibers increased antioxidant capacity and improved sensory quality of juice. Biopreservatives significantly reduced native microflora of fiber-enriched juices. Fiber-enriched samples treated with vanillin showed high total phenolic content.